Effectiveness of Brief Online Education in Enhancing Parental Knowledge on Child Growth and Health Monitoring - Merita Arini; Edwin Tohaga; Erwin Astha Triyono; Harumi Iring Primastuti; Wan Hasliza Wan Mamat; Desiani Wahyu Utami; Warkim Sutarto; Fauzan Adima; Abdul Latif Kurniawan; Teuku Ilham Noeryosan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Monitoring children’s growth and development is essential, yet many parents face barriers in accessing reliable health education. While online learning offers potential solutions, evidence of its effectiveness remains limited, particularly in developing countries. This study assessed the impact of a pediatrician-led online session, consisting of a brief presentation and interactive discussion via Zoom, conducted in collaboration with a community clinic, on parental knowledge regarding child growth and health monitoring. Methods: A single-group pretest-posttest design was conducted with 77 eligible participants from a publicly accessible webinar in collaboration with a private clinic in Bantul, Yogyakarta, Indonesia. The intervention included a pediatrician-led session covering growth milestones, health indicators, and monitoring techniques. A ten-item online questionnaire was developed and validated for content by four experts using the Content Validity Index (CVI), resulting in an average S-CVI of 0.95. Wilcoxon Signed-Rank Test and effect size analysis were performed. Results: Participants’ knowledge significantly increased following the intervention (p = 0.001) with a medium to large effect size (r = 0.52). There was an improvement in participants’ knowledge scores from a median of 70 (IQR 60–80) to 100 (IQR 85–100). No significant differences were found across demographic variables such as age, gender, or occupation (p > 0.05). Conclusion: This study demonstrated a positive shift in parental knowledge after a brief Zoom-based session. The findings underscore the potential of accessible online education to initiate broader community involvement in child health monitoring. Sustained impact will require integration with ongoing education, system-level support, and attention to barriers such as digital access and health literacy.